2007
DOI: 10.3314/jjmm.48.85
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Chromomycosis Caused by Fonsecaea pedrosoi Presenting as a Small Plaque on the Left Upper Arm: a Review of Reported Cases of Dematiaceous Fungal Infection in Japan

Abstract: We report a case of a 67-year-old woman with chromomycosis on the left upper arm. The plaque was a very small, erythematous and scaly lesion with a diameter of 1.5 cm. Fonsecaea pedrosoi was isolated as the causal fungus, and a number of Phialophora type conidia, the formation of which is considered rare, were observed. Treatment involved surgical excision of the lesion with a 5 mm margin. Follow up three years later revealed no recurrence. In Japan, 536 patients with chromomycosis were reported from 1955 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…In Japan, Fonsecaea pedrosoi, E. dermatitidis and E. jeanselmei are predominant agents of phaeohyphomycosis [3]. We report an unusual case of phaeohyphomycosis of the face caused by the recently recognized species Exophiala oligosperma.…”
Section: Clinical Lettermentioning
confidence: 97%
“…In Japan, Fonsecaea pedrosoi, E. dermatitidis and E. jeanselmei are predominant agents of phaeohyphomycosis [3]. We report an unusual case of phaeohyphomycosis of the face caused by the recently recognized species Exophiala oligosperma.…”
Section: Clinical Lettermentioning
confidence: 97%
“…De Hoog et al state that the former distinction between F. pedrosoi and F. compacta is no longer accepted because the latter is now considered a morphologic variant of the former [21]. A number of papers have appeared in the literature reporting on CBM cases caused by Exophiala spp., making it clear that this genus should be accepted among the causative agents [23][24][25][26][27][28][29][30]. Quite recently, Zhang et al [31] reported on three cases diagnosed in China, caused by Fonsecaea monophora, a species previously described in association with CBM only once [32].…”
Section: Historymentioning
confidence: 98%
“…Continuous topical thermotherapy has been described and is used almost exclusively by Japanese authors [30,[119][120][121][122]. The method is based on fungal intolerance to higher temperatures and uses pocket warmers placed over the lesion 24 h/day, for several months until disease is cured.…”
Section: Continuous Topical Thermotherapymentioning
confidence: 99%
“…109 Surgical excision with antifungal treatment may be appropriate for small lesions, whereas larger lesions may require 5-flucytosine plus oral thiabendazole, amphotericin B, or an oral triazole. 101,110 Thermotherapy is not an uncommon treatment for chromomycosis, either as monotherapy or as an adjunct to systemic antifungals in refractory cases.…”
Section: Subcutaneous Mycosesmentioning
confidence: 99%